Research of gas release during crystallization of aluminium and its alloys - Трегубенко, Геннадий Николаевич (Technology audit and production reserves, 2015)
The problem of gas porosity formation in the manufacture of aluminum structural or cast porous alloys is discussed and some results of our research in this area are shown in the article. The main aim of the research is to investigate the influence of various technological, physical and chemical factors on the process of hydrogen gas release during crystallization of aluminum and its alloys. Using system simulation allows a scientist to investigate fully the flow of a process. In this paper to simulate the process of hydrogen gas release it was considered the simplest and, therefore, the most discussed in the literature option when the crystallization front moves in an unlimited amount of melt. The presented method allows determining what factors and how affecting the process of hydrogen gas release during production of aluminum castings and its alloys. The research results can be applied by experts in the field of metal technology, metallurgy, foundry, production of aluminum castings for mechanical engineering.